1999
DOI: 10.1038/sj.ejcn.1600701
|View full text |Cite
|
Sign up to set email alerts
|

Iron status of middle-aged women in five counties of rural China

Abstract: Objective: To determine the relationships of dietary iron sources, other dietary factors, and lifestyle to iron status among premenopausal and recently postmenopausal Chinese women with widely varying regional dietary patterns. Design: Cross-sectional. Subjects were interviewed, blood samples were drawn, and dietary intakes were measured by a 3-day dietary survey for subjects in the ®ve survey counties. Setting: Rural China Subjects: About 80 randomly selected subjects per county among women aged 32 ± 66 y. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
5
15
1
Order By: Relevance
“…Table 2 summarises studies that investigated the association between tea consumption and iron status in women. No significant associations between high tea consumption and low iron status parameters were found in a European study (Van de Vijver et al, 1999) and in a Chinese study (Root et al, 1999) with a low percentage of iron deficient women. The cross-sectional study (Van de Vijver et al, 1999) among European girls (n ¼ 1080; mean 13.5 y) and young women (n ¼ 524; mean 22.0 y) from six countries focused on the association between calcium intake and iron status.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Table 2 summarises studies that investigated the association between tea consumption and iron status in women. No significant associations between high tea consumption and low iron status parameters were found in a European study (Van de Vijver et al, 1999) and in a Chinese study (Root et al, 1999) with a low percentage of iron deficient women. The cross-sectional study (Van de Vijver et al, 1999) among European girls (n ¼ 1080; mean 13.5 y) and young women (n ¼ 524; mean 22.0 y) from six countries focused on the association between calcium intake and iron status.…”
Section: Resultsmentioning
confidence: 90%
“…Tea and coffee consumption was not significantly associated with serum ferritin. The Chinese study (Root et al, 1999) showed that women can adapt successfully to a wide range of iron intakes and bioavailability. Root et al, (1999) examined the iron status of middle-aged Chinese women (n ¼ 400; 32 -66 y old) randomly selected from five counties in rural China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No data, to the best of our knowledge, on postnatal iron intake for rural Chinese postpartum women are available from the literature. Previous studies have showed that the daily total iron intake of rural Chinese women is around 20 ± 30 mgaday, of which non-haem iron is the main iron source (Root et al 1999;Ge et al, 1995). Although the consumption of the special dish is common for Guangdong postpartum women, the increased consumption of other haem iron sources eg poultry, meat and eggs, during the early postpartum period is commonly practised by the rural Chinese women of other provinces, eg Chongqing (Chen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%